-4(-4u+9)-2u=4(u-8)-6

Simple and best practice solution for -4(-4u+9)-2u=4(u-8)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-4u+9)-2u=4(u-8)-6 equation:


Simplifying
-4(-4u + 9) + -2u = 4(u + -8) + -6

Reorder the terms:
-4(9 + -4u) + -2u = 4(u + -8) + -6
(9 * -4 + -4u * -4) + -2u = 4(u + -8) + -6
(-36 + 16u) + -2u = 4(u + -8) + -6

Combine like terms: 16u + -2u = 14u
-36 + 14u = 4(u + -8) + -6

Reorder the terms:
-36 + 14u = 4(-8 + u) + -6
-36 + 14u = (-8 * 4 + u * 4) + -6
-36 + 14u = (-32 + 4u) + -6

Reorder the terms:
-36 + 14u = -32 + -6 + 4u

Combine like terms: -32 + -6 = -38
-36 + 14u = -38 + 4u

Solving
-36 + 14u = -38 + 4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-4u' to each side of the equation.
-36 + 14u + -4u = -38 + 4u + -4u

Combine like terms: 14u + -4u = 10u
-36 + 10u = -38 + 4u + -4u

Combine like terms: 4u + -4u = 0
-36 + 10u = -38 + 0
-36 + 10u = -38

Add '36' to each side of the equation.
-36 + 36 + 10u = -38 + 36

Combine like terms: -36 + 36 = 0
0 + 10u = -38 + 36
10u = -38 + 36

Combine like terms: -38 + 36 = -2
10u = -2

Divide each side by '10'.
u = -0.2

Simplifying
u = -0.2

See similar equations:

| y+x+26=64 | | 3(y+2)=-2(5y-1)+7y | | a^2-a-2=0 | | 0=3x^3+x^2-38x+24 | | x+26-y=64 | | 12-45x=8-12x | | 2m+26=9m-2 | | -2(2v-4)+7v=7+3(7v-5) | | 23=6v-1 | | y=19x+6 | | =0.4x^2*2+10 | | 2=-v-4 | | 7/10x=-14/3 | | -2(u+3)=4u-6+2(3u+5) | | X+10=2x+10 | | 8x-10y=0 | | 16-5(3+-9)=-2+19 | | 25x^2=125x | | 3(y-6)-6=-2(-8y+9)-9y | | y=0.4x^2*2+10 | | y=0.4x^22+10 | | -36=5x-18-4 | | -5(2u-8)+9u=7(u+5) | | -5/2x-4=-x-1 | | 4x^4+14xy+2y^2= | | x+2x+2+3x+4=180 | | 5x+2-7x=10+2x | | x=33-2x | | x=32-2x | | 3+5(2y-3)=-2(3y-3)+2y | | i=3i-16 | | 20u+30v= |

Equations solver categories